2019
DOI: 10.1080/15381501.2019.1607795
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic disparities associated with awareness, access, and usage of Pre-Exposure Prophylaxis among Latino MSM ages 21–30 in San Antonio, TX

Abstract: HIV continues to disproportionately affect Latino men who have sex with men (MSM) and disparities are even greater in the South. This study examines the implications of socioeconomic status (SES) associated with awareness, access, and usage of PrEP. Latino MSM (N=154) from San Antonio, TX completed a self-administered survey. Results revealed that PrEP uptake was significantly lower for low SES Latino MSM. PrEP related barriers included lack of awareness, stigmas, and side effects. Findings underscore the impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…As previously noted, one major barrier to PrEP implementation among Latinx SMM, is the lack of culturally adapted information and awareness surrounding this biomedical prevention (Barreras et al, 2019; Garcia & Saw, 2019). This is particularly relevant for Latinx SMM who face additional barriers associated with lower socioeconomic status (SES; Garcia & Saw, 2019). Garcia and Saw (2019) document that overall, Latinx SMM with lower SES were more likely to be severely underserved and uninformed on PrEP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As previously noted, one major barrier to PrEP implementation among Latinx SMM, is the lack of culturally adapted information and awareness surrounding this biomedical prevention (Barreras et al, 2019; Garcia & Saw, 2019). This is particularly relevant for Latinx SMM who face additional barriers associated with lower socioeconomic status (SES; Garcia & Saw, 2019). Garcia and Saw (2019) document that overall, Latinx SMM with lower SES were more likely to be severely underserved and uninformed on PrEP.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly relevant for Latinx SMM who face additional barriers associated with lower socioeconomic status (SES; Garcia & Saw, 2019). Garcia and Saw (2019) document that overall, Latinx SMM with lower SES were more likely to be severely underserved and uninformed on PrEP. At the individual level, Latinx SMM who were primarily Spanish-speaking were also significantly less likely to be aware of PrEP (Brooks, Nieto, et al, 2019; Mansergh et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Socioeconomic challenges, poor health care access, and stigma are direct barriers to HIV prevention efforts in Black and Hispanic/Latinx populations. Socioeconomic difficulties may include inability to afford health insurance or co-pays, a lack of transportation access to health care providers, and a relative absence of health care serving organizations in socioeconomically deprived areas ( Garcia & Saw, 2019 ; Ransome et al, 2016 ; Turner et al, 2019 ). These difficulties, driven in part by discrimination in employment, education, income, and housing, create challenges in accessing and using health care ( Logie et al, 2018 ).…”
Section: Summary Of Black and Hispanic/latinx Disparitiesmentioning
confidence: 99%
“…Hispanics or Latino/a/x are less likely to be knowledgeable of their HIV status, achieve HIV viral suppression, and engage in pre-exposure prophylaxis (PrEP) [ 1 , 5 ]. A study conducted in San Antonio, TX, US indicated that Hispanic or Latino/a/x sexual minority males with a higher socioeconomic status (SES) were more likely to be aware of PrEP, but fears of being stigmatized as promiscuous discouraged them from enrolling in PrEP [ 6 ]. The same study found that Hispanic or Latino/a/x sexual minority males with a lower SES were less aware of PrEP and less likely to consider PrEP due to it being considered an experimental drug, medical side effects, and government mistrust [ 6 ].…”
Section: Introductionmentioning
confidence: 99%